Analisis Hambatan Komunikasi Dalam Pemulihan Sosial Ekonomi Pasca Bencana Di Kampung Tanjung Kabupaten Pesisir Selatan - Maylasandi, Tifa; Sulastri, Irta; ., Hermawati (Jurnal Kajian Islam dan Sosial Keagamaan, 2024)
Pesisir Selatan Regency is an area that is potentially prone to disasters, especially floods and landslides. Disasters have a significant impact, especially on the economic sector. The Regional Government has tried to overcome this impact, especially in post-disaster economic recovery, but there are still several obstacles that mean the results are not fully optimal. This difficulty was mainly caused by the government's decision to relocate communities affected by the disaster to Nagari Silaut, Silaut District. This approach creates a number of communication problems between the government and local residents. The community feels that they do not receive clear and transparent information regarding the relocation process, the reasons behind choosing a new location, as well as guarantees of safety and welfare in the new place. Misunderstanding and distrust between the two parties caused the crisis management process to not run as quickly and efficiently as expected. This research aims to identify effective solutions offered in handling natural disaster crises. Through a study of development communication and community empowerment, this research uses a qualitative methodology with a phenomenological research approach, data is collected using observation, documentation and interview techniques. Qualitative data analysis was carried out using interactive data analysis techniques according to Miles and Huberman. The research results show that the post-disaster economic recovery strategy for the people of Kampung Tanjung in Pesisir Selatan Regency includes borrowing excavator machines, basic food assistance and collecting data on house repairs for disaster victims.